Total Phenolics, Flavonoids, Tannin Contents and Antioxidant Properties of Pleurotus ostreatus Cultivated on Different Wastes and Sawdust - Ayşenur Yılmaz; Sibel Yıldız; Ceyhun Kılıç; Zehra Can (International Journal of Secondary Metabolite)
In this study, the usage possibilities of some agro-industrial wastes such as; peanut wastes, potatoes farm wastes, walnut and orange tree sawdust in Pleurotus ostreatus cultivation were investigated and total phenolic, flavonoid, condensed  tannin content and antioxidant properties of these methanolic mushroom extracts were examined. For the determination of the total phenolic contents, the Folin-Ciocalteau procedure was used. The content of total flavonoid present in the methanolic extracts was measured using a spectrophotometric assay. Condensed tannins were determined according to the method by Julkunen-Tıtto. The antioxidant capacity was determined using ferric reducing antioxidant power (FRAP) and free radical scavenging activity of DPPH. The highest total phenolic content (2.672 ± 0.003 mg GAE/g) was found in mushroom cultivated on walnut sawdust. The highest condensed tannin (1.011 ± 0.088 CE mg/g) and ferric reducing antioxidant power (FRAP) (12.332 ± 0.017 μmol FeSO4.7H2O/g) were observed in the same mushroom extract. The highest total flavonoid and free radical scavenging activity of DPPH were found in extract of mushroom cultivated on potatoes handle. Bioactive properties of P. ostreatus cultivated on walnut tree sawdust were generally exhibited remarkable results.